Full-doping-amount graphite tailing ultra-high performance concrete and preparation method thereof
By using the combination of full-adult graphite tailings with cement, fume, and ultra-fine fly ash microbeads in ultra-high-performance concrete, the concrete performance is regulated, and the problem of low graphite tailings is solved, and efficient utilization is achieved. Improved performance, alleviating environmental pollution.
Patent Information
- Application Number
- CN202411350511.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-26
AI Technical Summary
In the prior art, graphite tailings are used in the preparation of ultra-high performance concrete and cannot be used efficiently, resulting in graphite tailings accumulation and environmental pollution problems.
The preparation method of fully-added graphite tailings ultra-high performance concrete is used to regulate the matrix density and working performance of concrete through the combination of cement, silica fume, ultra-fine fly ash microbeads and high-efficiency water reducing agent, and prepare excellent Concrete with mechanical properties.
Effective utilization of graphite tailings has improved the mechanical properties and working properties of ultra-high performance concrete, and alleviated the accumulation and environmental pollution of graphite tailings.
Smart Images

Figure BDA0005062224170000041 
Figure BDA0005062224170000051 
Figure BDA0005062224170000061
Abstract
Description
Technical Field
[0001] The invention belongs to the field of ultra-high performance concrete, and specifically relates to a full-dosage graphite tailings ultra-high performance concrete and a preparation method thereof. Background Art
[0002] Ultra-high performance concrete (UHPC) has ultra-high mechanical properties, ultra-high durability and high impermeability. It is regarded as one of the most excellent cement-based composite materials in the past thirty years and is a hot research direction in the current civil engineering materials and structural research fields. Usually, all coarse aggregates are removed from UHPC preparation, and only a large amount of fine sand with a particle size of less than 0.6 mm is used as aggregate filling. The total amount of fine aggregate used is about 1200kg / m 3 , which is much larger than ordinary concrete. Although this optimizes the uniformity of the matrix, the high demand for fine sand significantly increases the preparation cost and energy consumption, hindering the further promotion and use of UHPC.
[0003] In the process of graphite mining and processing, there are a large number of solid slag graphite tailings, which are huge. Graphite is mined by flotation method, and about 13 tons of graphite tailings are produced for purifying 1 ton of graphite. The long-term accumulation of graphite tailings occupies land and deteriorates the surrounding environment, erodes the soil, and the dust generated causes air pollution. As a major producer, China accounts for more than 50% of the global graphite production. Taking 2022 as an example, the world's graphite output is 1.3 million tons, and China's output accounts for about 65%, which means that China's graphite tailings emissions in 2022 alone will reach more than 10.985 million tons.
[0004] Graphite tailings have a certain research foundation in the preparation of traditional building production raw materials such as building bricks, cement, mortar concrete and ceramics. Taking the research results of literature such as "The Current Status of Graphite Tailings Resource Utilization", "Optimization Analysis of Graphite Tailings Cement Mortar Mix Ratio", and "Study on Mechanical Properties and Conductive Properties of Graphite Tailings Concrete" as examples, due to technical limitations, the optimal dosage of graphite tailings to replace traditional aggregates in the preparation of cement-based composites is roughly between 10% and 20%, and the specific dosage is 0-200kg / m 3 The components of UHPC involve a variety of granular materials such as aggregate, quartz powder, cement, fly ash, silica fume, etc. Reasonable matching of these materials can make the composite particles achieve the best chemical composition and physical properties matching form, which is conducive to enhancing the mechanical properties and durability of UHPC. Summary of the invention
[0005] The present invention aims to solve the problem that when graphite tailings are used to prepare concrete in the current cement-based composite material field, the amount of graphite tailings used is low and the graphite tailings cannot be used efficiently, and further provide a full-dosage graphite tailings ultra-high performance concrete and a preparation method thereof.
[0006] A full-doped graphite tailings ultra-high performance concrete consists of 773-950 parts of cement, 140-240 parts of silica fume, 180-240 parts of ultrafine fly ash microbeads, 1142-1333 parts of graphite tailings, 31.2-50.4 parts of high-efficiency water reducing agent, 0-4.8 parts of defoaming agent and 240-264 parts of water in parts by mass.
[0007] The above-mentioned method for preparing a kind of ultra-high performance concrete with full addition of graphite tailings is specifically carried out according to the following steps:
[0008] 1. Weigh 773-950 parts of cement, 140-240 parts of silica fume, 180-240 parts of ultrafine fly ash microspheres, 1142-1333 parts of graphite tailings, 31.2-50.4 parts of high-efficiency water reducing agent, 0-4.8 parts of defoaming agent and 240-264 parts of water as raw materials by mass;
[0009] 2. Add cement, silica fume, ultrafine fly ash microbeads and graphite tailings into a mixer to obtain aggregates, and pre-mix the aggregates for 120 seconds to make the aggregates dry-mixed evenly;
[0010] 3. Mix the high-efficiency water reducing agent, defoaming agent and water to obtain an admixture mixture, divide the admixture mixture into two parts according to the mass ratio of 80% and 20%, add 80% of the admixture mixture into the mixer and stir for 180s, stop stirring, add 20% of the admixture mixture into the mixer and stir for 300s, then turn off the mixer, discharge the material, prepare test pieces, and perform curing to obtain full-dosage graphite tailings ultra-high performance concrete.
[0011] Beneficial effects of the present invention:
[0012] The present invention uses graphite tailings as all aggregates to prepare ultra-high performance concrete, which helps to promote the application of ultra-high performance concrete and alleviate the ecological problems caused by the large-scale accumulation of graphite tailings to a large extent.
[0013] The present invention uses a ternary cementitious material system consisting of cement-fly ash microbeads-silica fume to regulate the matrix density of graphite tailings UHPC, and successfully prepares a fully-doped graphite tailings UHPC with excellent mechanical properties by utilizing the interaction between different particles.
[0014] The present invention regulates the working performance of graphite tailings UHPC by reasonably regulating the amount of mixing water and the amount of admixture, and successfully prepares a fully-dosed graphite tailings UHPC with excellent working performance. DETAILED DESCRIPTION
[0015] Specific implementation method 1: In this implementation method, a full-dosage graphite tailings ultra-high performance concrete is composed of 773 to 950 parts of cement, 140 to 240 parts of silica fume, 180 to 240 parts of ultrafine fly ash beads, 1142 to 1333 parts of graphite tailings, 31.2 to 50.4 parts of high-efficiency water reducer, 0 to 4.8 parts of defoamer and 240 to 264 parts of water by mass.
[0016] Specific embodiment 2: This embodiment is different from the specific embodiment 1 in that the concrete is composed of 888 parts of cement, 144 parts of silica fume, 192 parts of ultrafine fly ash microspheres, 1176 parts of graphite tailings, 40.8 parts of high-efficiency water reducing agent, 2.4 parts of defoaming agent and 246 parts of water by mass. The rest is the same as the specific embodiment 1.
[0017] Specific implementation method three: This implementation method is different from the specific implementation method one in that the cement is P.Ⅱ52.5 ordinary Portland cement, with a 28d compressive strength of 55.75MPa, a 28d flexural strength of 7MPa, and a density of 3100kg / m 3 The rest is the same as the first specific implementation mode.
[0018] Specific embodiment 4: This embodiment differs from specific embodiment 1 in that the graphite tailings are produced in Jixi City, Heilongjiang Province, and the particle size ranges from 0 to 0.6 mm. Other aspects are the same as those of specific embodiment 1.
[0019] Specific implementation mode 5: This implementation mode is different from the specific implementation mode 1 in that the water is tap water. The rest is the same as the specific implementation mode 1.
[0020] Specific embodiment 6: This embodiment is different from the specific embodiment 1 in that the properties of the silica fume are: water requirement ratio is 125%, loss on ignition ratio is 1.45%, and apparent density is 2214kg / m 3 , with a specific surface area of 19500m 2 / kg; the 7-day activity index is 107%, and the 28-day activity index is 122.5%. Other aspects are the same as those of the first embodiment.
[0021] Specific embodiment 7: The difference between this embodiment and specific embodiment 1 is that the properties of the ultrafine fly ash microspheres are: water demand ratio is 90%, loss on ignition ratio is 0.2%, and apparent density is 2500kg / m 3 , with a specific surface area of 2431m 2 / kg; the 7-day activity index is 80%, and the 28-day activity index is 115%. Other aspects are the same as those of the first embodiment.
[0022] Specific embodiment eight: This embodiment differs from specific embodiment one in that: the high-efficiency water reducing agent is a polycarboxylic acid high-performance water reducing agent, the actual water reduction rate is 30%, and the solid content is 25%; the defoaming agent is a white powder, the pH value is 7.0, and the defoaming performance is measured to be 1.907 g / mL. Others are the same as specific embodiment one.
[0023] Specific implementation method 9: In this implementation method, a method for preparing a full-dosage graphite tailings ultra-high performance concrete is specifically carried out according to the following steps:
[0024] 1. Weigh 773-950 parts of cement, 140-240 parts of silica fume, 180-240 parts of ultrafine fly ash microspheres, 1142-1333 parts of graphite tailings, 31.2-50.4 parts of high-efficiency water reducing agent, 0-4.8 parts of defoaming agent and 240-264 parts of water as raw materials by mass;
[0025] 2. Add cement, silica fume, ultrafine fly ash microbeads and graphite tailings into a mixer to obtain aggregates, and pre-mix the aggregates for 120 seconds to make the aggregates dry-mixed evenly;
[0026] 3. Mix the high-efficiency water reducing agent, defoaming agent and water to obtain an admixture mixture, divide the admixture mixture into two parts according to the mass ratio of 80% and 20%, add 80% of the admixture mixture into the mixer and stir for 180s, stop stirring, add 20% of the admixture mixture into the mixer and stir for 300s, then turn off the mixer, discharge the material, prepare test pieces, and perform curing to obtain full-dosage graphite tailings ultra-high performance concrete.
[0027] Specific embodiment 10: This embodiment differs from specific embodiment 9 in that the speed of the stirrer in step 2 is kept constant at 60 r / min. The rest is the same as specific embodiment 9.
[0028] The effect of the present invention is verified by the following experiments:
[0029] The specific raw materials and specifications used in the embodiments and comparative examples are as follows:
[0030] The cement is P.Ⅱ52.5 ordinary Portland cement, with a 28d compressive strength of 55.75MPa, a 28d flexural strength of 7MPa, and a density of 3100kg / m 3 . The particle size range of graphite tailings is 0-0.6mm. The experimental water is ordinary tap water. The water reducer is a polycarboxylic acid high-performance water reducer with an actual water reduction rate of 30% and a solid content of 25%. The defoaming agent is XP-2 type high-efficiency solid defoaming powder, a white powder with a pH value of 7.0 and a defoaming performance of 1.907g / mL. The water requirement ratio of silica ash experimental supplies is 125%, the ignition loss ratio is 1.45%, and the apparent density is 2214kg / m 3, with a specific surface area of 19500m 2 / kg; 7d activity index is 107%, 28d activity index is 122.5%. Fly ash microbead particle size experimental supplies, water requirement ratio is 90%, ignition loss ratio is 0.2%, apparent density is 2500kg / m 3 , with a specific surface area of 2431m 2 / kg, the 7-day activity index was 80%, and the 28-day activity index was 115%.
[0031] The mixer adopts GMP50 vertical shaft planetary mixer with a rotation speed of 60r / min.
[0032] Raw material ingredients
[0033] Chemical composition of the cementitious material used in this test (%)
[0034]
[0035] Experimental methods:
[0036] 1. Working performance: The expansion of fresh UHPC is tested in accordance with the "Standard for Test Methods of Ordinary Concrete Mixture Performance GB / T 50080-2002".
[0037] 2. Mechanical properties: The compressive strength and flexural strength of fresh UHPC are tested in accordance with the "Test method for strength of cement mortar (ISO method) GB / T 17871-2021".
[0038] method:
[0039] 1. Add cement, silica fume, ultrafine fly ash microbeads and graphite tailings into a mixer to obtain aggregates, and pre-mix the aggregates for 120 seconds to make the aggregates dry-mixed evenly;
[0040] 2. Mix a high-efficiency water reducing agent, a defoaming agent and water to obtain an admixture mixture, divide the admixture mixture into two parts according to a mass ratio of 80% and 20%, add 80% of the admixture mixture into a mixer and stir for 180 seconds, stop stirring, add 20% of the admixture mixture into the mixer and stir for 300 seconds, then turn off the mixer, discharge the material, prepare test pieces, and perform curing to obtain full-dosage graphite tailings ultra-high performance concrete.
[0041] Specific implementation case 1:
[0042] In this embodiment, there are 240 parts of water, 870 parts of cement, 1200 parts of graphite tailings, 141 parts of silica fume, 188 parts of microspheres, 40.8 parts of water reducing agent, and 2 parts of defoaming agent.
[0043] Comparative Example 1:
[0044] The difference from Example 1 is that the amount of mixing water in the mix ratio is changed to 246 parts.
[0045] Comparative Example 2:
[0046] The difference from Example 1 is that the amount of mixing water in the mix ratio is changed to 252 parts.
[0047] Comparative Example 3:
[0048] The difference from Example 1 is that the amount of mixing water in the mix ratio is changed to 258 parts.
[0049] Comparative Example 4:
[0050] The difference from Example 1 is that the amount of mixing water in the mix ratio is changed to 264 parts.
[0051] The test results are shown in the table.
[0052] Table 1
[0053]
[0054] Combined with Table 1, we can see the experimental results and analysis:
[0055] As shown in Table 1, as the proportion of mixing water gradually increases from 240 to 264, the flexural and compressive strengths of ultra-high-strength concrete show a significant downward trend, and the 28d compressive strength of Comparative Example 4 is only 86% of the 28d strength of the specimen of Example 1. However, the fluidity is greatly improved with the increase of the water-binder ratio.
[0056] Specific implementation case 2:
[0057] In this embodiment, water 230 parts, cement 774 parts, graphite tailings 1333 parts, silica fume 125 parts, microspheres 167 parts, water reducer 36 parts, defoamer 2 parts, that is, the mortar-sand ratio is 0.8. The water reducer and water are liquids, and the rest are solids. Stir at a speed of 60r / min.
[0058] Comparative Example 5:
[0059] The difference from Example 2 is that the number of graphite tailings is changed to 1263 parts, the number of cement is changed to 824 parts, the number of silica fume is changed to 133 parts, and the number of microbeads is changed to 178 parts, that is, the mortar-sand ratio is changed to 0.9, and the ratio between the cementitious materials remains unchanged.
[0060] Comparative Example 6:
[0061] The difference from Example 2 is that the number of graphite tailings is changed to 1200 parts, the number of cement is changed to 870 parts, the number of silica fume is changed to 141 parts, and the number of microbeads is changed to 188 parts, that is, the mortar-sand ratio is changed to 1.0, and the ratio between the cementitious materials remains unchanged.
[0062] Comparative Example 7:
[0063] The difference from Example 2 is that the number of graphite tailings is changed to 1142 parts, the number of cement is changed to 912 parts, the number of silica fume is changed to 147 parts, and the number of microbeads is changed to 197 parts, that is, the mortar-sand ratio is changed to 1.1, and the ratio between the cementitious materials remains unchanged.
[0064] Comparative Example 8:
[0065] The difference from Example 2 is that the number of graphite tailings is changed to 1090 parts, the number of cement is changed to 949 parts, the number of silica fume is changed to 154 parts, and the number of microbeads is changed to 205 parts, that is, the mortar-sand ratio is changed to 1.2, and the ratio between the cementitious materials remains unchanged.
[0066] Table 2
[0067]
[0068] Experimental results and analysis:
[0069] As shown in Table 2, the 28d compressive and flexural strength of concrete changes little with the change of mortar-sand ratio, and the trend is not obvious. However, when the number of graphite tailings is 1090, the strength changes significantly. The expansions of specific examples 2 to comparative examples 8 are 633, 745, 839, 873, and 928 mm, respectively, and the fluidity gradually increases with the increase of cementitious materials.
[0070] Specific implementation case three:
[0071] In this embodiment, 258 parts of water, 1080 parts of cement, 1200 parts of graphite tailings, 120 parts of silica fume, 40.8 parts of water reducing agent, and 2 parts of defoaming agent are used. The water reducing agent and water are liquids, and the rest are solids, and the mixture is stirred at a speed of 60 r / min.
[0072] Comparative Example 9:
[0073] The difference from Example 3 is that the amount of silica fume is changed to 180 parts.
[0074] Comparative Example 10:
[0075] The difference from Example 3 is that the amount of silica fume is changed to 240 parts.
[0076] Comparative Example 11:
[0077] The difference from Example 3 is that the amount of silica fume is changed to 300 parts.
[0078] Comparative Example 12:
[0079] The difference from Example 3 is that the amount of silica fume is changed to 360 parts.
[0080] Table 3
[0081]
[0082] Experimental results and analysis:
[0083] As shown in the data in Table 3, compared with the 28d strength of the specimen of Comparative Example 12, the 28d strength of Comparative Example 9 reaches 117.6%, and the strength is significantly improved. When the proportion of silica fume exceeds 180, as the proportion of silica fume mass increases, the flexural and compressive strengths of ultra-high-strength concrete show a significant downward trend. According to the data, the optimal replacement amount of silica fume should be between 120 and 240 parts of cementitious materials. The expansion of this group is (903-803-700-673-642), which shows that silica fume has greater water absorption, and a higher proportion leads to a decrease in fluidity.
[0084] Specific implementation case 4:
[0085] In this embodiment, 258 parts of water, 960 parts of cement, 1200 parts of graphite tailings, 120 parts of silica fume, 120 parts of microspheres, 40.8 parts of water reducing agent, and 2 parts of defoaming agent are used. The water reducing agent and water are liquids, and the rest are solids, and the mixture is stirred at a speed of 60 r / min.
[0086] Comparative Example 13:
[0087] The difference from Example 4 is that the number of microbeads is changed to 180.
[0088] Comparative Example 14:
[0089] The difference from Example 4 is that the number of microbeads is changed to 240.
[0090] Comparative Example 15:
[0091] The difference from Example 4 is that the number of microbeads is changed to 300.
[0092] Comparative Example 16:
[0093] The difference from Example 4 is that the number of microbeads is changed to 360.
[0094] Table 4
[0095]
[0096] Experimental results and analysis:
[0097] As shown in Table 4, the increase in the number of microspheres will slightly reduce the compressive and flexural strength of UHPC. However, microspheres have the function of improving the fluidity of concrete. The expansion of this group is (768-820-873-980-847). It can be seen that even a slight increase in the proportion of microspheres will greatly improve the fluidity. Considering the compressive strength, flexural strength and working performance, the optimal amount of microspheres is between 120 and 180 parts.
[0098] Specific implementation case five:
[0099] In this embodiment, water 258 parts, cement 870 parts, graphite tailings 1200 parts, silica fume 141 parts, micro beads 188 parts, water reducer 31.2 parts, defoamer 2 parts. Water reducer and water are liquids, and the rest are solids, and stirred at a speed of 60r / min.
[0100] Comparative Example 17:
[0101] The difference from Example 5 is that the number of water reducing agent parts is changed to 36 parts.
[0102] Comparative Example 18:
[0103] The difference from Example 5 is that the amount of water reducing agent is changed to 40.8 parts.
[0104] Comparative Example 19:
[0105] The difference from Example 5 is that the amount of water reducing agent is changed to 45.6 parts.
[0106] Comparative Example 20:
[0107] The difference from Example 5 is that the amount of water reducing agent is changed to 50.4 parts.
[0108] Table 5
[0109]
[0110]
[0111] Experimental results and analysis:
[0112] As shown in Table 5, with the gradual increase of water reducing agent, the flexural and compressive strength of concrete first increased and then decreased. The 28d strength of comparative example 18 is 116.9% of the 28d strength of example 5. According to data analysis, the most suitable water reducing agent content is between 31.2 and 40.8 parts. With the increase of high-efficiency water reducing agent, the working performance first increased and then decreased. The expansion of this group is (713-745-833-770-753). When the water reducing agent reaches 40.8 parts, the fluidity has increased slightly as the dosage continues to increase.
[0113] Specific implementation case six:
[0114] In this embodiment, water 258 parts, cement 870 parts, graphite tailings 1200 parts, silica fume 141 parts, micro beads 188 parts, water reducer 40.8 parts, defoamer 0 parts. Water reducer and water are liquids, and the rest are solids, and stirred at a speed of 60r / min.
[0115] Comparative Example 21:
[0116] The difference from Example 6 is that the amount of defoaming agent is changed to 2.4 parts.
[0117] Comparative Example 22:
[0118] The difference from Example 6 is that the amount of defoaming agent is changed to 4.8 parts.
[0119] Comparative Example 23:
[0120] The difference from Example 6 is that the amount of defoaming agent is changed to 7.2 parts.
[0121] Comparative Example 24:
[0122] The difference from Example 6 is that the amount of defoaming agent is changed to 9.6 parts.
[0123] Table 6
[0124]
[0125] Experimental results and analysis:
[0126] As shown in the data in Table 6, with the increase in the amount of defoaming agent, the flexural and compressive strengths of the ultra-high-strength concrete first increase and then decrease, reaching the maximum value of the experimental data in Comparative Example 21, which is 122.2% of Comparative Example 24. Therefore, it is speculated that the optimal amount of defoaming agent added is between 2.1 and 4.8 parts.
[0127] Specific implementation case seven:
[0128] In this embodiment, water 258 parts, cement 720 parts, graphite tailings 1200 parts, silica fume 480 parts, micro beads 0 parts, water reducer 40.8 parts, defoamer 2 parts. Water reducer and water are liquids, and the rest are solids, and stirred at a speed of 60r / min.
[0129] Comparative Example 25:
[0130] The difference from Example 7 is that the amount of silica fume is changed to 360 parts and the amount of microbeads is changed to 120 parts.
[0131] Comparative Example 26:
[0132] The difference from Example 7 is that the amount of silica fume is changed to 240 parts and the amount of microbeads is changed to 240 parts.
[0133] Comparative Example 27:
[0134] The difference from Example 7 is that the amount of silica fume is changed to 120 parts and the amount of microbeads is changed to 360 parts.
[0135] Comparative Example 28:
[0136] The difference from Example 7 is that the amount of silica fume is changed to 0 parts, and the amount of microbeads is changed to 480 parts.
[0137] Table 7
[0138]
[0139] Experimental results and analysis:
[0140] As shown in Table 7, as the amount of silica fume decreases and the amount of microspheres increases, the fluidity of UHPC gradually increases. The expansion of this group is (716-745-807-851-882), because the addition of microspheres improves the overall fluidity, and the decrease in silica fume content makes the overall water demand less scarce, and the fluidity increases. In terms of mechanical properties, with the changes in the two, the compressive strength and flexural strength show a trend of first increasing and then decreasing, reaching the maximum value in comparative example 26, indicating that there is an optimal ratio between the amount of silica fume and microspheres, which should be around 1:1.
[0141] Performance Optimization
[0142] Based on the mix ratio range: 773-950 parts of cement, 1142-1333 parts of graphite tailings, 240-264 parts of water, 31.2-40.8 parts of water reducer, 2.4-4.8 parts of defoamer, 180-240 parts of silica fume, and 180-240 parts of microspheres. The MAA model was used to optimize the mix ratio according to the particle grading of graphite tailings, cement, silica fume and microspheres, and a mix ratio was obtained. The mixing water, water reducer and defoamer dosage were adjusted to obtain the following mix ratio:
[0143] The mix ratio is 246 parts of water, 888 parts of cement, 1176 parts of graphite tailings, 144 parts of silica fume, 192 parts of microspheres, 40.8 parts of water reducer, and 2.4 parts of defoamer.
[0144]
[0145] According to the above research scope, the flexural strength and compressive strength of the graphite tailings UHPC mix optimized by MAA are significantly improved, with a 28d flexural strength of 16.84MPa and a 28d compressive strength of 120.73, reaching the maximum compressive strength in all experimental groups. Its expansion is 645mm, which is in line with the category of self-compacting concrete. If there are higher requirements for fluidity, the amount of water reducer and mixing water can be further adjusted according to the scope of the present invention.
Claims
1. A full-doped graphite tailings ultra-high performance concrete, characterized in that The concrete consists of 773-950 parts of cement, 140-240 parts of silica fume, 180-240 parts of ultrafine fly ash beads, 1142-1333 parts of graphite tailings, 31.2-50.4 parts of high-efficiency water reducing agent, 0-4.8 parts of defoaming agent and 240-264 parts of water in parts by mass.
2. A full-dosage graphite tailings ultra-high performance concrete according to claim 1, characterized in that The concrete consists of 888 parts of cement, 144 parts of silica fume, 192 parts of ultrafine fly ash beads, 1176 parts of graphite tailings, 40.8 parts of high-efficiency water reducing agent, 2.4 parts of defoaming agent and 246 parts of water by mass.
3. A full-dosage graphite tailings ultra-high performance concrete according to claim 1, characterized in that The cement is P.Ⅱ52.5 ordinary Portland cement, with a 28d compressive strength of 55.75MPa, a 28d flexural strength of 7MPa, and a density of 3100kg / m 3 .
4. The ultra-high performance concrete with full addition of graphite tailings according to claim 1, characterized in that Graphite tailings are produced in Jixi City, Heilongjiang Province, with a particle size range of 0 to 0.6 mm.
5. The full-dosage graphite tailings ultra-high performance concrete according to claim 1, characterized in that The water is tap water.
6. The full-dosage graphite tailings ultra-high performance concrete according to claim 1, characterized in that The properties of the silica fume are as follows: water requirement ratio is 125%, loss on ignition ratio is 1.45%, and apparent density is 2214kg / m 3 , with a specific surface area of 19500m 2 / kg; the 7-day activity index was 107%, and the 28-day activity index was 122.5%.
7. The full-dosage graphite tailings ultra-high performance concrete according to claim 1, characterized in that The properties of the ultrafine fly ash microbeads are: water requirement ratio of 90%, loss on ignition ratio of 0.2%, apparent density of 2500kg / m 3 , with a specific surface area of 2431m 2 / kg; the activity index at 7 days was 80%, and the activity index at 28 days was 115%.
8. The full-dosage graphite tailings ultra-high performance concrete according to claim 1, characterized in that The high-efficiency water reducer is a polycarboxylic acid high-performance water reducer, with an actual water reduction rate of 30% and a solid content of 25%; the defoamer is a white powder with a pH value of 7.0 and a defoaming performance of 1.907 g / mL.
9. The method for preparing a fully mixed graphite tailings ultra-high performance concrete according to claim 1, characterized in that The preparation method of full-dosage graphite tailings ultra-high performance concrete is specifically carried out according to the following steps:
1. Weigh 773-950 parts of cement, 140-240 parts of silica fume, 180-240 parts of ultrafine fly ash microspheres, 1142-1333 parts of graphite tailings, 31.2-50.4 parts of high-efficiency water reducing agent, 0-4.8 parts of defoaming agent and 240-264 parts of water as raw materials by mass; 2. Add cement, silica fume, ultrafine fly ash microbeads and graphite tailings into a mixer to obtain aggregates, and pre-mix the aggregates for 120 seconds to make the aggregates dry-mixed evenly; 3. Mix the high-efficiency water reducing agent, defoaming agent and water to obtain an admixture mixture, divide the admixture mixture into two parts according to the mass ratio of 80% and 20%, add 80% of the admixture mixture into the mixer and stir for 180s, stop stirring, add 20% of the admixture mixture into the mixer and stir for 300s, then turn off the mixer, discharge the material, prepare test pieces, and perform curing to obtain full-dosage graphite tailings ultra-high performance concrete.
10. The method for preparing a fully mixed graphite tailings ultra-high performance concrete according to claim 9, characterized in that In step 2, the stirring speed is kept constant at 60 r / min.
Citation Information
Patent Citations
High-strength anti-cracking thermal construction concrete material and preparing method thereof
CN108264278A
Preparation method of high-temperature-resistant concrete material capable of effectively resisting fire damage as well as product and application of high-temperature-resistant concrete material
CN118388184A
Cited By
Ultra-high performance concrete based on high-valued utilization of ground graphite tailings and preparation method of ultra-high performance concrete
CN119977479A
